KONFLIK ALAT TANGKAP ANTAR NELAYAN DI DESA TELUK PAMBANG KECAMATAN BANTAN KABUPATEN BENGKALIS PROVINSI RIAU - Pebri Karisma (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This article explores on: (1) analyze fisherman between conflict social root in management fishery resource; (2) explore social impact conflict happened by inside fishermen society in Riau Desa Teluk Pambang Kecamatan Bantan Kabupaten Bengkalis Provinsi; (4) study social intelligence for fisherman between conflict resolution. Fisherman between conflict happened in Desa Teluk Pambang influenced by instrumentation arrest that not suit with law Permen Nomor KP 70 Tahun 2016. Until, have the impact to seashore ecosystem crumble, social jealousy, social disintegration, and conflict regeneration. In potential incorporate intelligence as Bengkalis Kabupaten government conflict resolution had workshop activity handling on a resource, held meeting Dinas Perikanan Riau and Partisipatif MCS uses to get fisherman agreement